Pemanfaatan Aplikasi Google Earth dalam Pembelajaran Sejarah di SMA Negeri 6 Tangerang - Zakia Salsabila; Aisiah Aisiah (Jurnal Kronologi, 2026)
This study aims to describe the utilization of the Google Earth application in history learning and to analyze its role in supporting students' spatial understanding and engagement. The research employed a qualitative approach with a descriptive method conducted at SMA Negeri 6 Tangerang. The research subjects consisted of five history teachers and 34 students from class X.A3. Data collection techniques included observation, interviews, and documentation. Data analysis was performed through data reduction, data display, and conclusion drawing, using triangulation techniques to ensure data validity. The results indicate that the utilization of Google Earth contributes to assisting students in understanding the spatial aspects of historical events through more concrete location visualizations. Furthermore, the use of this medium supports students' active involvement in the learning process through exploration, discussion, and analysis activities. The findings also suggest that learning has the potential to become more contextual and interactive, although its implementation is still influenced by the availability of facilities and teacher readiness.